Optimalisasi Laba UMKM Melalui Manajemen Keuangan - Adeh Ratna Komala (Indonesian Community Service and Empowerment Journal (IComSE), 2022)
The purpose of this service is to provide training to manage business profits for Micro, Small and Medium Enterprises (MSEs) in the Bandung area as many as 200 participants. The implementation method is carried out virtually via zoom us where at the end of the session participants are given the opportunity to ask questions related to problems in managing finances. The material provided is related to the stages in managing finances, namely: separate business capital from own capital, all recorded correctly, financial statements are prepared including statements of financial position, comprehensive income statements, statements of changes in equity and cash flow statements. This is done so that business operations are well controlled. This activity is organized by the Accounting Student Association (HMAk UNIKOM). The result of this service is that the participants of Micro, Small and Medium Enterprises (MSEs) are greatly helped in managing their business profits. The material presented becomes the basis for participants in improving their business financial records. The participants were also given additional material in using social media to market their products, The conclusion of this activity is very beneficial for Micro, Small and Medium Enterprises (MSEs) actors in managing their business finances so that the sustainability of their business is maintained. Key words: MSEs, profit optimization, social media